Extended main sequence turnoffs in open clusters as seen by Gaia – I. NGC 2818 and the role of stellar rotation. Issue 3 (2nd August 2018) - Bastian, N; Kamann, S; Cabrera-Ziri, I; Georgy, C; Ekström, S; Charbonnel, C; de Juan Ovelar, M; Usher, C
ABSTRACT: We present an analysis of the relatively low mass (∼2400 M⊙ ), ∼800 Myr, Galactic open cluster, NGC 2818, using Gaia DR2 results combined with VLT/FLAMES spectroscopy. Using Gaia DR2 proper motions and parallax measurements, we are able to select a clean sample of cluster members. This cluster displays a clear extended main sequence turn-off (eMSTO), a phenomenon previously studied mainly in young and intermediate age massive clusters in the Magellanic clouds. The main sequence of NGC 2818 is extremely narrow, with a width of ∼0.01 magnitudes ( G BP – G RP ), suggesting very low levels of differential extinction. Using VLT/FLAMES spectroscopy of 60 cluster members to measure the rotational velocity of the stars ( V sin i ), we find that stars on the red side of the eMSTO have high V  sin i (>160 km s −1 ) while stars on the blue side have low V  sin i (<160 km s −1 ), in agreement with model predictions. The cluster also follows the previously discovered trend between the age of the cluster and the extent of the eMSTO. We conclude that stellar rotation is the likely cause of the eMSTO phenomenon.